The Characteristics Of Impaired Physical Mobility Among Patients With Stroke - I Gede Purnawinadi (Klabat Journal of Nursing, 2019)
A valid nursing diagnosis is very important in nursing care. Clinical indicators are required to validate nursing diagnoses to reduce the risk of misdiagnosis. The accuracy of clinical indicators is determined by the limitation of characteristics and related factors. The purpose of this study was to describe the characteristics nursing diagnosis of impaired physical mobility. This research was a descriptive study conducted by assessment through observation in clinical practice. There were 20 records of stroke patient documentation used in this study. The results showed that the limitations of the main characteristics that emerged in stroke patients were dyspnea after activity (90%), gait disorder (100%), slow motion (100%), spastic movements (100%), uncoordinated movements (100%), posture instability (100%), difficulty flipping position (100%), limited range of motion (100%), discomfort (100 %), decreased fine motoric skills (90%), decreased gross motoric skills (100%), and moving tremor (90%). Nurses are expected to focus on main characteristics that arise during the assessment of stroke patients with nursing diagnoses of impaired physical mobility in order to plan effective nursing actions. For further investigators it is recommended to use valid instruments in conducting the assessment so that these characteristics can be a more accurate indicator in nursing diagnosis.